Foliar treatments with Gaultheria procumbens essential oil induce defense responses and resistance against a fungal pathogen in Arabidopsis - Vergnes, Sophie; Ladouce, Nathalie; Fournier, Sylvie; Ferhout, Hicham; Attia, Faouzi; Dumas, Bernard (Frontiers in Plant Science, 2014)
Essential oil from Gaultheria procumbens is mainly composed of methylsalicylate (>96%), a compound which can be metabolized in plant tissues to salicylic acid, a phytohormone inducing plant immunity against microbial pathogens. The potential use of G. procumbens essential oil as a biocontrol agent was evaluated on the model plant Arabidopsis thaliana. Expression of a selection of defence genes was detected 1, 6 and 24 hours after essential oil treatment (0.1 ml/L) using a high-throughput qPCR-based microfluidic technology. Control treatments included methyl jasmonate and a commercialized salicylic acid analog, benzo(1,2,3)-thiadiazole-7carbothiolic acid (BTH). Strong induction of defence markers known to be regulated by the salicylic acid pathway was observed after the treatment with G. procumbens essential oil. Treatment induced the accumulation of total salicylic acid in the wild -type Arabidopsis line Col-0 and analysis of the Arabidopsis line sid2, mutated in a salicylic acid biosynthetic gene, revealed that approximately 30% of methylsalicylate sprayed on the leaves penetrated inside plant tissues and was demethylated by endogenous esterases. Induction of plant resistance by G. procumbens essential oil was tested following inoculation with a GFP-expressing strain of the Arabidopsis fungal pathogen Colletotrichum higginsianum. Flurorescence measurement of infected tissues revealed that treatments led to a strong reduction (60%) of pathogen development and that the efficacy of the G. procumbens essential oil was similar to the commercial product BION®. Together, these results show that the G. procubens essential oil is a natural source of methylsalicylate which can be formulated to develop new biocontrol products.